2021
DOI: 10.3390/md19080468
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Effects of Mytilus coruscus Polysaccharide on RAW264.7 Cells and DSS-Induced Colitis in Mice

Abstract: Considerable literature has been published on polysaccharides, which play a critical role in regulating the pathogenesis of inflammation and immunity. In this essay, the anti-inflammatory effect of Mytilus coruscus polysaccharide (MP) on lipopolysaccharide-stimulated RAW264.7 cells and a dextran sulfate sodium (DSS)-induced ulcerative colitis model in mice was investigated. The results showed that MP effectively promoted the proliferation of RAW264.7 cells, ameliorated the excessive production of inflammatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…These results demonstrated that DGDG-LAHLA suppressed the production of both pro-inflammatory and anti-inflammatory cytokines. Such simultaneous suppression of both pro-inflammatory and anti-inflammatory cytokines has been reported for several other compounds (e.g., tribulusamide D [ 21 ] and Mytilus coruscus polysaccharide [ 22 ]). In these studies, the inhibition of an upstream transcription factor, NF-κB, was suggested as an underlying mechanism.…”
Section: Resultsmentioning
confidence: 52%
“…These results demonstrated that DGDG-LAHLA suppressed the production of both pro-inflammatory and anti-inflammatory cytokines. Such simultaneous suppression of both pro-inflammatory and anti-inflammatory cytokines has been reported for several other compounds (e.g., tribulusamide D [ 21 ] and Mytilus coruscus polysaccharide [ 22 ]). In these studies, the inhibition of an upstream transcription factor, NF-κB, was suggested as an underlying mechanism.…”
Section: Resultsmentioning
confidence: 52%
“…In mice with dextran sodium sulphate-induced ulcerative colitis (DSS) after treatment with MP, the integrity of the intestinal barrier and the Firmicutes/Bacteroidetes ratio were improved; there was also a greater abundance of some probiotics, such as Anaerotruncus , Lactobacillus, Desulfovibrio , Alistipe, Odoribacter , and Enterorhabdus , in the colon. Thus, MP could be a promising dietary candidate for treating ulcerative colitis and improving immunity [ 109 ].…”
Section: Macroorganisms As Source Of Immunomodulatory Compoundsmentioning
confidence: 99%
“…Currently, several marine polysaccharides show potential in alleviating insulin resistance. In our previous study, we reported the potential of active polysaccharides in mussels in alleviating inflammation and regulating intestinal flora 21‐23 . Based on those findings, we used T2D as the research object and continued to explore its impact on glucose and lipid metabolism disorders and microbiota changes.…”
Section: Introductionmentioning
confidence: 99%